Erratum to: Soft Tissue Phantoms for Realistic Needle Insertion: A Comparative Study (Annals of Biomedical Engineering, 10.1007/s10439-015-1523-0) - Leibinger,A; Forte,AE; Tan,Z; Oldfield,MJ; Beyrau,F; Dini,D; Rodriguez,y Baena F (Annals of Biomedical Engineering, 2016)
Reference 4 should be changed to: Forte, A. E., S. Galvan, F. Manieri, F. Rodriguez y Baena, and D. Dini. A composite hydrogel for brain tissue phantoms. Mater. Des. 227:238–112, 2016.